Influence of Emergent Vegetation Layout on Flow Pattern in a Rectangular Shallow Basin - Junnan LYU; Yuxuan JIANG; Zhidong YAO; Chen YE; Xufeng YAN (工程科学与技术)
Objective Shallow basins, varying in natural and artificial forms, are prevalent in urban and rural areas. They play critical roles in ecology, water resource management, environmental protection, and enhancing landscape aesthetics. For instance, wetlands and ponds become hubs for fish, plants, and plankton; reservoirs store water for agricultural irrigation, drinking, and industrial uses; constructed wetlands and ponds facilitate the removal of pollutants and harmful chemicals; and landscape ponds and lakes, adorned with vegetation, increase the real estate value. Prior research has extensively debated shallow basins’ functions and influencing factors from these perspectives, employing methods such as field investigations, aerial remote sensing, physical experiments, large-scale modeling, and surveys. Despite achievements in addressing individual perspectives, a comprehensive, systematic study covering multiple aspects remains lacking. The hydrodynamics within a shallow basin dictate its efficiency in treatment, water exchange rate, and the ratio of stagnant water areas. Hence, numerous strategies have been employed to enhance the hydraulic performance of shallow basins. Altering the aspect ratio, for example, can adjust the stagnant water ratio, enhancing or impairing the basin’s hydraulic function. Elliptical basins are recognized for their superior hydraulic performance over rectangular ones. In addition, aquatic vegetation, whether emergent or submerged, is acknowledged to enhance the hydraulic performance of shallow basins by equalizing flow velocity as water spreads laterally upon entering the basin. From the landscape design perspective, strategically interspersing aquatic vegetation is believed to elevate the aesthetic appeal of the basin and its vegetation. However, a detailed quantitative analysis of the impact of vegetation’s spatial distribution remains unexplored, leaving room for optimizing vegetation layout for hydraulic efficiency and landscape beauty.Methods This study focuses on how various spatial arrangements of emergent aquatic vegetation affect the hydraulic performance of shallow basins, aiming to identify an optimal vegetation design. The basin shape is limited to a rectangle with a fixed width-to-length ratio (width: 4 m and length: 6 m), and the dimensions of inlet and outlet were standardized. The depth-averaged Reynolds Averaged Navier–Stokes equations with the k-ε turbulence model are applied to simulate water movement within the shallow basin. Experimental data from existing literature, specifically velocity distributions, are initially utilized for model validation. In addition, the study examines the independence of results from grid size to ensure modeling consistency.Based on the validation of the velocity profile from flume tests, the two-dimensional shallow water model can reliably simulate flow within shallow pools and successfully capture the flow patterns of circulations where the main stream adheres to one sidewall while developing asymmetrically on both sides. Incorporating a vegetation drag term into the momentum equations allows the simulation of flow dynamics influenced by emergent vegetation.Results and Discussions In order to examine the impact of vegetation’s spatial distribution on flow patterns within a shallow basin, five vegetation distribution scenarios are conceptualized: 1) complete coverage, 2) lateral full coverage with variable longitudinal partial coverage downstream of the inlet (LFVLPI), 3) lateral full coverage with variable longitudinal coverage downstream of the outlet (LFVLPO), 4) longitudinal full coverage with variable symmetrical lateral partial coverage (LFVSLP), and 5) localized vegetation coverage near the inlet. In the case of complete coverage, the influence of vegetation density is assessed to identify the threshold at which a plug flow pattern (or absence of dead water zones) emerges. The findings indicated a transition from bare to vegetated conditions, where an asymmetrical flow pattern featuring two distinct circulation sizes (or dead water zones) evolves into a symmetrical flow pattern with similar circulations. As vegetation density reaches a threshold of 5 m−1, circulations vanish, yielding a plug flow pattern. This density threshold surpasses those reported in previous studies. Upon reaching this critical vegetation density, the impact of various spatial distributions of vegetation, with constant density, on flow patterns is explored. For LFVLPI, reducing the vegetation coverage ratio from full coverage does not alter the plug pattern until the ratio diminishes to 1/8, at which point small circulations appear near the basin’s inlet. In contrast, with LFVLPO, circulations persist, characterized by a pair of large cells and a pair of small corner cells. For LFVSLP, only small corner circulations form. As lateral coverage lessens, these corner cells scarcely enlarge until vegetation is absent. The minimal local vegetation coverage necessary for establishing a plug flow pattern occurs when the lateral coverage ratio is 1/2 and the longitudinal ratio is 1/4. Further analysis of the center-axis longitudinal velocity and its gradient along the basin’s length is conducted to indicate the formation of the plug flow pattern in response to hydraulic adjustments due to the introduction of vegetation. The evolution of circulation zones is closely linked to the rate of longitudinal velocity adjustment upon water entering the basin. A rapid local decrease in velocity leads to a swift global homogenization, significantly reducing the velocity shear or adverse pressure gradient between the center and surrounding zones. Consequently, introducing vegetation can eliminate flow circulations or dead water zones if it causes a rapid velocity decrease in the area following the inlet. In addition, examining the relationship between the proportion of the circulating water body area Ar and the dimensionless mean velocity gradient $(\Delta U U_{\mathrm{m}}^{-1}) /(L_{\mathrm{a}} L^{-1}) $ , which demonstrates flow adjustment, revealed a significant logarithmic correlation between the two metrics (R2=93%).Conclusions The results demonstrate that emergent vegetation can be applied to suppress flow circulation in shallow basins, which improves shallow basin flow pattern. Its mechanism is identified that the porous vegetation can effectively uniformize the flow velocity transversely after the flow enters into the basin. The spatial distribution of the vegetation and its density in combination play a significant role. A logarithmic model Ar=0.45ln[ $(\Delta U U_{\mathrm{m}}^{-1}) /(L_{\mathrm{a}} L^{-1})$ ]−2.5 is found to offer guidance for the hydraulic design of rectangular shallow basins with selective vegetation distribution.